Integrating seismic acoustic impedance inversion and attributes for reservoir analysis over ‘DJ’ Field, Niger Delta - Ayodeji Alabi; Pius Adekunle Enikanselu (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Structural interpretation and inversion analysis were used to characterize hard-to-image reservoirs, to predict subsurface interwell reservoir properties for optimum reservoir heterogeneity description, and to fine-tune drilling locations in ‘DJ’ Field, Niger Delta. Post-stacked 3D seismic data, composite well logs, and velocity checkshot data were used for the reservoir analysis. The study entailed mapping of structural framework, horizon picking, wavelet extraction, log editing and correlation, building of low-frequency model, acoustic impedance inversion and crossplot analysis of reservoir properties. Four major antithetic, three regional, and five minor faults were identified. The inversion results revealed an acoustic impedance range of 9700–25,000 ft/s g/cc and porosity range of 25–45% within the hydrocarbon-bearing sands. Crossplot analysis of Poisson and Vp/Vs ratio against acoustic impedance revealed Poisson ratio range of 0.30–0.45 and V p/V s ratio range of 1.3–2.50 within the delineated hydrocarbon-bearing sandstone interval. The overall correlation coefficient between the inverted and actual impedance was about 98% across the eight wells. Acoustic impedance slice at 2300 ms revealed low acoustic impedance sand within the range of 13,000–24,000 ft/s g/cc at the western and central part of the field. Comparing the acoustic impedance slice and seismic attribute maps at the target reservoir zones revealed high reflection amplitudes (bright Spots), indicative of hydrocarbon accumulation. The study predicts new and reliable drillable locations, by lithologic/fluid discrimination in the analysis of delineated reservoirs in the study area.